2002
DOI: 10.2337/diacare.25.4.724
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study and Open-Label Extension Evaluating the Long-Term Efficacy of Pramlintide as an Adjunct to Insulin Therapy in Type 1 Diabetes

Abstract: OBJECTIVE -To assess the effect of mealtime amylin replacement with pramlintide on long-term glycemic and weight control in patients with type 1 diabetes. RESEARCH DESIGN AND METHODS-In a 52-week, double-blind, placebocontrolled, multicenter study, 480 patients with type 1 diabetes were randomized to receive preprandial injections of placebo or 30 g pramlintide q.i.d., in addition to existing insulin regimens. At week 20, pramlintide-treated patients were re-randomized to 30 or 60 g pramlintide q.i.d. if decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
260
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(274 citation statements)
references
References 36 publications
10
260
2
2
Order By: Relevance
“…A dose of 120 μg was chosen because it has been widely studied in long-term trials [33][34][35], it has been shown to elicit a sustained reduction in body weight [33][34][35][36], and is intended for clinical use in insulin-treated subjects with type 2 diabetes. The preload meal consisted of 125 g of banana blended with 150 ml of low-fat (2%) milk and 150 ml of water (estimated energy content ∼189 kcal; 6 g protein, 36 g carbohydrate, 3 g fat), and was consumed within 3 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dose of 120 μg was chosen because it has been widely studied in long-term trials [33][34][35], it has been shown to elicit a sustained reduction in body weight [33][34][35][36], and is intended for clinical use in insulin-treated subjects with type 2 diabetes. The preload meal consisted of 125 g of banana blended with 150 ml of low-fat (2%) milk and 150 ml of water (estimated energy content ∼189 kcal; 6 g protein, 36 g carbohydrate, 3 g fat), and was consumed within 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the observed glucoregulatory actions of amylin in rodents, clinical studies in insulin-treated patients with diabetes have shown that pramlintide reduces postprandial glucose excursions by suppressing glucagon secretion and slowing gastric emptying [30][31][32]. In long-term (6-12 months) clinical studies of insulin-treated type 1 or type 2 diabetic patients, adjunctive treatment with pramlintide lowered HbA 1 c levels and produced a significant and sustained reduction in body weight, particularly in those patients who were overweight at baseline [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, pramlintide reduces food intake in both T1D and control subjects (Asmar et al 2010) and induces sustained weight loss in T1D subjects (Whitehouse et al 2002, Ratner et al 2005, Edelman et al 2006. However, given the modest phenotype of IAPPdeficient animals, physiologically IAPP is likely a minor contributor to overall satiety and may act to fine-tune the more robust effects of other satiety signals.…”
Section: Iapp Replacement In Type 1 Diabetesmentioning
confidence: 99%
“…Pramlintide can significantly decrease post-meal glucagon levels in type 1 diabetes mellitus and trials have also shown that pramlintide reduces glucose variability by delaying gastric emptying. [51][52][53][54][55] …”
Section: Amylinmentioning
confidence: 99%